PENERAPAN METODE CRITICAL CHAIN PROJECT MANAGEMENT UNTUK PERENCANAAN PROYEK VERY LOW PRESSURE PHASE-II KEI Ltd - Nasution, Siti Rohana; -, Resthy (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
This research is do to make Very Low Pressure Phase-II Project which be expected to not like the last project which have not appropriate between plan and implementation. It is because the increase of activity which is not planned before and student’s syndrome behavior. Student’s syndrome like spin out time is occur because the safety time in every activity and when a project have a problem, with the result that the estimation time and cost is bigger. Therefore, it be made a plan with applied Critical Chain Project Management method. From primer data and secondary data be treated with microsoft project software. This method is to hide safety time in every activity and change with buffer time. Increase buffer time with using cut and paste method is add project buffer half of critical chain duration at the end of chain and put feeding buffer with half activity to activity at not critical chain which bring it to critical chain. The result of research is when a project is already start and no changes, so the project can finish during 370 day with cost 3,558,232.73 USD. When the project is not appropriate, then buffer time can be consumed about 185 day with resource buffer cost about 334,767.27 USD and total of finished project is 555 day, a safety time for Very Low Pressure Phase-II project.